Breaking the Chains: Unveiling the Gender Pay Gap through Socialist Feminism and Intersectionality in Aotearoa New Zealand - Maulana, Palupi (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2025)
This essay explores the intricate landscape of the gender pay gap in Aotearoa New Zealand, delving into the complexities through the lenses of socialist feminism and intersectionality. Despite New Zealand's commitment to gender equality since the introduction of the Equal Pay Act in 1972, persistent disparities remain, particularly for Māori and Pacific women. The socialist feminist perspective uncovers the roots of gender-based oppression intertwined with broader class-based inequalities, emphasizing the need for a unified labor movement. Simultaneously, intersectionality reveals that pay gaps are shaped by intersecting identities such as gender, race, and ethnicity. Māori and Pacific women face heightened challenges due to systemic racism and discrimination. To address these issues, policy initiatives are suggested, advocating for an intersectional approach that includes minimum wage increases, universal basic income, childcare support, and enhanced parental leave policies. The essay concludes by emphasizing the importance of recognizing and rectifying in-work poverty and promoting a collective, intersectional approach to achieve full gender parity in Aotearoa New Zealand. Keywords: Gender pay gap, Socialist feminism, Intersectionality, Aotearoa New Zealand, Gender equality policies